The Correlation Between Customers Satisfaction And Brand Loyalty Toward IM3 - Nuraini Ratnaningtyas Amarsa (Jurnal Manajemen Indonesia, 2020)
High customer turnover rates and intense competition among cellular service companies make companies compete to get loyal customers, one of which is done by IM3 cellular services. Complaints escalation will make customers dissatisfied. This study discusses customer satisfaction, loyal customers, and the relationship between customers, namely customer satisfaction and loyalty to the IM3 brand. This study uses a non-experimental research design with correlational research methods. The results show that there is a significant relationship to the highest value and customer satisfaction which contributes more than the total brand loyalty score. The aspect of IM3 customer satisfaction most related to brand loyalty is the aspect of price and feature variations. The majority of customers want IM3 product performance to match their expectations. Related, Between customer satisfaction and customer loyalty has a positive relationship. Keywords—Input maximum five words or phrase; in alphabetical; separated by semicolon